ARQUEOLOGIA NO ESTADO DE SÃO PAULO: O SÍTIO TURVO (Revista Tópos, 2013)
Este artigo foi escrito com base no Relatório Final do Projeto de Iniciação Científica intitulado “A Arqueologia no Estado de São Paulo: Sítio Turvo”. O Sítio Arqueológico Turvo faz parte de um complexo de cinco sítios arqueológicos localizados no Município de Cardoso, norte do Estado de São Paulo. Foram coletados 1.338 fragmentos cerâmicos e 37 líticos, os quais foram levados para laboratório e analisados. Após análise técnica e estudo bibliográfico, chegou-se a conclusão de que aquela área foi ocupada por indígenas pertencentes a Tradição Aratu, caracterizada, entre outros, por sua cerâmica simples e sem decoração. A Tradição Aratu foi evidenciada por Valentin Calderón no Recôncavo Baiano e se estendeu por boa porção do território brasileiro, desde o Maranhão, passando pelo Mato Grosso até o norte do Estado de São Paulo. Palavras-chave: Arqueologia, Sítio Turvo, cerâmica Aratu.   Abstract This article was wrote based on a Scientifically Project Final Report entitled “Archeology in São Paulo`s State: Turvo Site”. Turvo Archeology Site is part of a complex of five archeology sites located in Cardoso city, north of São Paulo State. There, it was collected 1.338 ceramic fragments and 37 lithic who were taken to the lab where it was analyzed. After the technical analysis added to a bibliographical study, was concluded that that area was occupied by indigenes of Aratu Tradition, characterized for your simple ceramic, no decoration on that etc. Aratu Tradition was evidenced by Valentin Canderón in the Bahia and went on a large portion of the Brazilian territory, from Maranhão, Mato Grosso until passing through the northern state of São Paulo. This project also had for the initiative the Patrimonial Education at the public schools and the research divulgation in congress and other events. Key-words: Archeology, Turvo Site, Aratu Ceramic.